2015
DOI: 10.1519/jsc.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, But Not Acute Sleep Loss, Increases Salivary Antimicrobial Protein Secretion

Abstract: Sleep deficiencies may play a role in depressing immune parameters. Little is known about the impact of exercise after sleep deprivation on mucosal immunity. The purpose of this study was to quantify salivary antimicrobial proteins (AMPs) in response to sleep loss before and after exercise. Four men and 4 women (age: 22.8 ± 2; : 49.1 ± 7.1 ml · kg(-1) · min(-1)) completed 2 exercise trials consisting of 45 minutes of running at 75% VO2peak after a normal night of sleep (CON) and after a night without sleep (WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
2
22
2
Order By: Relevance
“…Contrary to our results, previous studies reported acute increases in the concentration of HNP1-3 determined immediately after submaximal constant intensity long duration protocols [7,9] or until 1 h compared to pre-exercise values [9]. The post exercise increase in salivary HNP1-3 levels may, to the same extent, be related to an exercise-induced muscle inflammatory response.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our results, previous studies reported acute increases in the concentration of HNP1-3 determined immediately after submaximal constant intensity long duration protocols [7,9] or until 1 h compared to pre-exercise values [9]. The post exercise increase in salivary HNP1-3 levels may, to the same extent, be related to an exercise-induced muscle inflammatory response.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants in the present investigation were master-age triathletes, while previous studies have analyzed the acute response of young recreationally active participants [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin and lysozyme, antimicrobial compounds found in saliva secretions [187,188], have been used to monitor longitudinal changes in elite weightlifters [189] and basketball players [190], measured in endurance exercise in which hydration affects secretion [191], and have been shown to increase in response to running at 75 % VO 2max [192]. Intense exercise, however, may reduce their concentration, which may subsequently increase the risk of infection and incidence of URTIs [83].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…In addition to insignificant effects of ambient/room temperature on the salivary lysozyme responses observed in this study, it was also noted that prolonged exercise, running at 60% for 90 min, have no significant effects on the salivary lysozyme responses. Similarly, a previous study has reported no change in salivary lysozyme after exercise, 14 while other investigators have reported significant increases 16 , 17 or decreases. 18 This discrepancy may be attributed to the different methods of expressing lysozyme, nutritional status of the participants, and the exercise protocol employed.…”
Section: Discussionmentioning
confidence: 72%